PEDAGOGICAL PRACTICES AND PROFESSIONAL GROWTH: THE IMPACT OF TECHNOLOGY ON TEACHING (CAHIERS MAGELLANES-NS, 2024)
This paper explores the transformative role of technology in shaping pedagogical practices and enhancing professional growth in the teaching profession. With the increasing integration of digital tools and platforms, educators are adapting their instructional methods to meet the evolving needs of learners. The study examines how technology fosters innovative teaching strategies, promotes collaboration, and enhances classroom engagement. It also delves into the professional development opportunities that arise from technology adoption, highlighting the need for continuous learning and adaptability among educators. Through a review of current practices and case studies, this paper seeks to demonstrate the profound impact of technology on both teaching methods and educators' professional trajectories, advocating for a balanced and reflective approach to technology integration in education.